Evaluation of usage and fuel savings of solar ovens in Nicaragua. (October 2016) - Bauer, Gordon
Abstract: Solar cooking technology has been promoted as a solution to both global poverty and environmental degradation, but relatively little research exists on the impact of solar oven usage on biomass fuel consumption. This study evaluates solar oven usage and wood consumption in northern Nicaragua during both the rainy and dry seasons, using surveys, temperature dataloggers, and direct measurements of fuelwood use. Solar oven owners reported usage on 79% of days during the dry season, and 41% of days during the rainy season. Comparison with oven temperature records confirmed usage on 50% of days during the dry season, and 16% of days during the rainy season. However, wood consumption measurements showed no statistically significant difference between days with solar oven usage and days without, suggesting that frequency of usage alone is not an appropriate proxy for fuel savings. Survey results suggest that a large part of solar oven usage came in addition to biomass cooking, as opposed to replacing it. These results suggest a need for further study of wood consumption in situ and more focus on the specific kinds of foods prepared in solar cookers, as well as local cultural and climatic conditions. Highlights: Solar oven usage reported on most days during dry season. No statistically significant fuelwood savings can be attributed to solar oven use. Usage reported on surveys differs substantially from solar oven temperature data. Possible causes of lack of wood savings range from weather to diet and gender norms.